Digital Marketing Strategy using White Hat SEO Techniques - Syarief Nur Husin; Primasatria Edastama; Amirsyah Tambunan (International Institute for Advanced Science & Technology (IIAST), 2022)
A journal service system's forum for a publisher platform, or journal publication, that disseminates data about scientific activity, is known as OJS (Open Journal System). By utilizing SEO, websites that already exist may also have their search engine rankings improved. Making it simpler for consumers to locate addresses for scientific journal websites is one technique to use White Hat SEO. This study tries to boost website traffic on sites that host scholarly journals. The White Hat SEO (Search Engine Optimization) strategy was employed in this study. This study was done on a website that had not yet implemented SEO strategies, then used White Hat SEO techniques such optimizing keywords in title tags, content, meta keywords, meta descriptions, and social media sharing. The outcomes of the examination of SEO implementation might make it easier to find websites for scientific journals.